A study on prevalence and risk factors associated with anaemia among school going adolescent girls in Chargawan block of Gorakhpur district - Singh, Parul; Tiwari, Harish C.; Sampriya, Arushi; Shrivastav, Arun K.; Shrivastav, Dhirendra K. (International Journal Of Community Medicine And Public Health, 2022)
Background: Adolescent anaemia is most common nutritional problem affecting the reproductive period, pregnancy and childbirth. Although there are several epidemiological studies to determine the prevalence and risk factors associated with anaemia among adolescent girls in India, but limited data regarding the prevalence and risk factors associated with anaemia in adolescent girls of Eastern Uttar Pradesh (UP) is available. To estimate the prevalence of anaemia among school going adolescent girls in Chargawan block of Gorakhpur district of UP and to study specific factors like sociodemographic factors, dietary factors and menstrual factors. Methods: A cross-sectional survey was conducted in the government higher secondary schools of Chargawan block, district Gorakhpur, UP. A total of 430 adolescent females (10-19 years old) were included in this study. The study took place from September 2019 to August 2020. In most of cases Chi-square test was applied as test of significance for comparing. Microsoft excel 2010 and statistical calculator has been used for statistical calculation. Results: The prevalence of anaemia found from this study was 61.39%. The statistically significant risk factors associated with anaemia were age, nuclear family, low socio-economic status, high intake of junk food; low intake of green leafy vegetables, citrus fruit, no iron folic acid intake and menorrhagia. Conclusions: A high prevalence of anaemia among adolescent females was found, which was higher in nuclear family, low socio economic strata; girls who were consuming less citrus fruits, less green leafy vegetables, more junk food and not taking any iron folic acid (IFA) supplement.